Alat Pengendali Arus pada Mesin DC-400 Berbasis Mikrokontroler dan Android - Didi Istardi; Muhammad Abdul Ghafur; Nugroho Pratomo Ariyanto (Politeknik Negeri Batam, 2018)
Power source is a device that serves to supply electrical current in type of welding SMAW (Shield Metal Arc Welding), an example is DC-400 machine. The output current of machine is set using a knob on the output control panel in order to generate heat as needed welding. Along with the development, welder realized that there are limitations in the way of controlling current on the machine. Distance control that requires users to go directly to the machine caused inefficiency in work. Therefore, we need a controller for adjusting the output current from long distance. It is necessary to create